Social constraints on human agency - Paraskevaides, Andreas (The University of Edinburgh, 2011)
In this thesis, I present a view according to which folk psychology is not only used for predictive and explanatory purposes but also as a normative tool. I take it that this view, which I delineate in chapter 1, can help us account for different aspects of human agency and with solving a variety of puzzles that are associated with developing such an account. My goal is to examine what it means to act as an agent in a human society and the way in which the nature of our agency is also shaped by the normative constraints inherent in the common understanding of agency that we share with other agents. As I intend to demonstrate, we can make significant headway in explaining the nature of our capacity to express ourselves authoritatively in our actions in a self-knowing and self-controlled manner if we place this capacity in the context of our social interactions, which depend on a constant exchange of reasons in support of our actions. My main objective is to develop a promising account of human agency within a folk-psychological setting by mainly focusing on perspectives from the philosophy of action and mind, while still respecting more empirically oriented viewpoints from areas such as cognitive science and neuroscience. Chapter 2 mainly deals with the nature of self-knowledge and with our capacity to express this knowledge in our actions. I argue that our self-knowledge is constituted by the normative judgments we make and that we use these judgments to regulate our behaviour in accordance to our folk-psychological understanding of agency. We are motivated to act as such because of our motive to understand ourselves, which has developed through our training as self-knowing agents in a folk-psychological framework. Chapter 3 explores the idea that we develop a self-concept which enables us to act in a self-regulating manner. I distinguish self-organization from selfregulation and argue that we are self-regulating in our exercises of agency because we have developed a self-concept that we can express in our actions. What makes us distinct from other self-regulating systems, however, is that we can also recognize and respond to the fact that being such systems brings us under certain normative constraints and that we have to interact with others who are similarly constrained. Chapter 4 is mainly concerned with placing empirical evidence which illustrate the limits of our conscious awareness and control in the context of our account of agency as a complex, emergent social phenomenon. Finally, chapter 5 deals with the way in which agentive breakdowns such as self-deceptive inauthenticity fit with this account.
Keywords: human agency; self-knowledge; self-regulation; folk psychology